Memory, meaning and hybrid culture of Johannesburg - Cutler, Gabrielle Elisheva (My University, 2018)
The project centres around ideas of memory in architecture, spatial politics, and the history of Johannesburg. It ivestigates the many historical layers of the city and those individuals, whose lives are marbled into those layers. As a representation of this narrative, the project explores the area of New Doornfontein. This area’s - east of the inner city - history and dense built fabric, act as a microcosm of a larger narrative of Johannesburg. Currently, the area is of mixed use, with an emphasis on activities alinged with Ellis Park (located north of the railway) and manufacturing. The proposed site is located south of the railway, at what used to be known as, ‘Mvuyana Yard’. Between the late 1800s and the Slums Removal Act of 1930, yards such as this could be found in residential suburbs at the edge of the city. Yards were spaces usually located at the back of residential properties. Small rooms - usually built from corrugated sheeting, timber, and sometimes brickwork - housed dense numbers of residents. The rooms were rented to races that would otherwise be segregated and living in designated areas, owing to the Natives’ Land Act. The rooms shared amenities and an outside space used for cooking and socializing. Based on the dense, ill-serviced living conditions the yards became known as “Urban Native Slumyards”. New Doornfontein housed six main yards, with the built fabric of none remaining, except that of Number 24 Lower Ross Street. This address housed a Pastor’s House and the African National Church, both built in 1922. Adjacent to this site, was the Central News Agency (CNA) compound, where workers would stay and delivery horses were stabled. Inclusive of these three premises, the project consolidates seven erven as the entire proposed site. The yards were, despite all intentions and efforts, the site of trans-cultural exchange. Despite its origins as a cultural adaptation, a form of cultural hybrid was born, giving way to new forms of identity and experience. Theories related to post-colonial hybridity support this societal phenomenon. Consequently, the society that arises from a mixture of ethnic groups forms a social new fabric. Examples of such adaptations manifest in linguistics, such as Fanakalo, as well as music, dance, and culture. This was the culture of the yards.This was the culture of Johannesburg. The atmosphere and historical recall of this period is well captured in Modikwe Dikobe’s (1973) novel; “The Marabi Dance”. The structure of his writing is similar to the proposed design approach. The story of the part can reflects the story of the whole. Dikobe’s spatial descriptions duly capture a built environment that only partially exists in present day New Doornfontein. The proposed design is a museum, a place for remembering, testifying, empowering, and performing. The project becomes relevant for the current community in New Doornfontein, who risk displacement due to the rapid gentrification of the area. Further, New Doornfontein’s built fabric is changing, and an awareness of this type of architectural erasure is necessary before the area’s heritage is disregarded. Ultimately, this project aims to integrate users and uses while interrogating the intentions of the site’s existing buildings. It is representative of the historic citizen of Johannesburg, while appropriating memory in present-day. Johannesburg is a hybrid city, representing a collective memory of its people.
Research Report submitted to the School of Architecture and Planning, University of the Witwatersrand, in fulfillment of the requirements for the Masters of Architecture (Professional). Submitted on 7 February 2018.